Biomechanical case study on toss up motion in tennis serve - Otsuka, E.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this case study was to suggest some coachings through the analysis of relationship between the ball toss and the whole body motion variability observed during the tennis serve. Comparing the standard deviation (SD) of impact location for each serve (flat serve, slice serve, and kick serve), in Y-axis direction (forward/backward), SD of flat serve was larger than slice and kick serve. To correspond such variability, subjects i) moved along the direction of variability, ii) did NOT adjust the trunk joint motion. The small angular motion of proximal segments, such as the trunk and upper arm, significantly affect the impact location. Therefore we encouraged players to use the translational motion of upper trunk to adjust the variability.